Trichlorfon-induced haematological and biochemical changes in Cyprinus carpio: ameliorative effect of propolis - Yonar, M. Enis; Yonar, Serpil Mise; Pala, Aysegul; Silici, Sibel; Saglam, Naim (Inter-Research, 2015)
Trichlorfon is among the most commonly used products to treat fish parasites in aquaculture. We investigated the effectiveness of propolis in alleviating the toxicity of trichlorfon on haematological and oxidant/antioxidant parameters in carp Cyprinus carpio. Fish were exposed to sublethal concentrations (11 and 22 mg l(-1)) of trichlorfon, and propolis (10 mg kg(-1) of fish weight) was simultaneously administered. At the end of 14 d administration, blood and tissue (liver, kidney, gill) samples were collected. Haematological changes (red and white blood cell count, haemoglobin concentration, haematocrit level and erythrocyte indices: mean corpuscular volume, mean corpuscular haemoglobin and mean corpuscular haemoglobin concentration) were determined in the blood samples, while antioxidant parameters (malondialdehyde and reduced glutathione levels and superoxide dismutase, catalase and glutathione peroxidase activities) were evaluated in the liver, kidney and gill samples. Trichlorfon led to negative alterations in the haematological and antioxidant parameters investigated. The administration of propolis alleviated this effect and suggests that fish treated with trichlorfon improve their physiological status when fed a propolis-supplemented diet.
Keywords: Organophosphate; Propolis; Haematology; Oxidative stress; Carp